The Anatomy of Start-Stop Growth - Jones, Benjamin F.; Olken, Benjamin A. (The Review of Economics and Statistics, 2008)
This paper investigates the remarkable extremes of growth experiences within countries and the changes that occur across growth transitions. We find two main results. First, virtually all but the very richest countries experience both growth miracles and failures over substantial periods. Second, growth accelerations and collapses are asymmetric phenomena. Collapses typically feature reduced investment amidst increasing price instability, whereas growth takeoffs are primarily associated with large expansions in international trade. The results show that even very poor countries regularly grow rapidly, but sustaining growth is difficult and may pose a very different set of challenges than starting it. Copyright by the President and Fellows of Harvard College and the Massachusetts Institute of Technology.